Antibacterial activities of the Methanolic extract of Bangladeshi Black tea against various human pathogens - Hossain, Mohammad Shahnoor; Nibir, Yead Morshed; Zerin, Sayma; Ahsan, Nazmul (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The goal of the present study was to evaluate the antibacterial activity of the methanolic extract of Bangladeshi black tea against various important pathogenic bacteria. Antibacterial activity test was carried out by agar well-diffusion method. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated using microdilution methods. Extract of Bangladeshi black tea demonstrated potential antibacterial activity in a dose dependent manner against all of the tested bacteria and exhibited highest activity against two common enteric pathogens, Shigella boydii and Vibrio cholerae with MIC and MBC of 200 ?g/ml and 1 mg/ml respectively. Our results indicate that black tea extract can be used as therapeutic to control these deadly pathogens. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21873 Dhaka Univ. J. Pharm. Sci. 13(1): 97-103, 2014 (June)